The Effects of Physical Exercise on the Quality of Life of Healthy Older Adults in China: A Systematic Review - Wei, Lin; Hu, Yongmei; Tao, Yingying; Hu, Rui; Zhang, Liancheng (Frontiers in Psychology, 2022)
Objective To systematically evaluate the effects of physical exercise on the quality of life (QOL) of healthy older adults in China. Methods Relevant articles published until December 2021 were retrieved from China National Knowledge Infrastructure, Wanfang, China Science and Technology Journal Database, PubMed, EBSCO, Web of Science, and the Library of Congress. Inclusion criteria were studies in which the subjects were healthy Chinese older adults (aged ≥ 60 years), the reported sample size was clear, and the study design was a randomized controlled trial or a research study. In addition, studies were included if they reported the use of at least one QOL questionnaire and investigated at least one form of physical exercise. Results In total, 19 studies met the inclusion criteria, which included six studies that used comprehensive physical exercise type as an intervention and 13 studies that used regular physical exercise as an intervention. All 19 studies compared intervention and control groups, of which 12 (63%) were investigative studies and seven (37%) were experimental studies. Of the experimental studies, five used a positive control group and two used a negative control group. All 19 studies reported that physical exercise had varying degrees of positive effects on the QOL in older adults. Body–mind exercise was effective in improving the physical and mental health (MH) of older adults, whereas Xiyangcao only had a positive effect on physical health. Compared with no exercise or other exercise (exercise not used in the intervention group), the exercise group in the survey had a positive effect on the QOL of older adults. Regardless of the type of control group used, the exercise group in the experimental studies showed a positive effect of exercise on the QOL of older adults. Conclusion Physical exercise has a positive impact on the QOL of healthy older adults. However, due to the wide and varied scope of the included studies, more randomized controlled trials are needed to examine the effects of different types, intensities, durations, and the frequency of exercise on QOL. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=220115], identifier: [CRD42020220115].